Digital Governance in Public Procurement in an Archipelagic Region: The Case of Bintan Regency - Hendra Saputra; O. Okparizan; Dedy Afrizal (Manunggal Halim Jaya, 2026)
Digital transformation within the public sector has driven a shift in procurement systems from manual procedures toward electronic-based services. One manifestation of this digitalization is the adoption of the e-Catalogue system in local government procurement processes. This study aims to examine the use of the e-Catalogue in supporting the transformation of procurement governance from a digital governance perspective in the Government of Bintan Regency. A qualitative approach with a descriptive method was employed. Data were collected through interviews, observation, and documentation involving officials engaged in the local government procurement process. The findings indicate that the use of the e-Catalogue contributes to accelerating procurement administrative processes, improving access to information on products and suppliers, and enhancing transparency and oversight, as all activities are digitally recorded. The implementation of the electronic system also encourages a shift in bureaucratic work patterns toward more structured and information technology–based practices. The effectiveness of e-Catalogue implementation is influenced by system usability, officials’ experience, socialization and training support from the procurement service unit (LPSE), and government policies on procurement digitalization. However, several challenges remain, including internet network disruptions, server instability, and varying levels of digital competency among officials in operating the system. The archipelagic geographic conditions further affect the quality of regional digital infrastructure. This study emphasizes that the adoption of the e-Catalogue is not merely a technical administrative innovation, but also reflects a broader transformation of governance toward a more efficient, transparent, and accountable digital government system.